Prevalencia de Ancylostoma caninum en perros domésticos en el área urbana y área rural de la parroquia Calceta - Pérez Tito, Jimmy Juvert (2025)
The objective of this study was to evaluate the prevalence of Ancylostoma caninum in domestic dogs in urban and rural areas of the Calceta parish and to identify risk factors based on an analysis of owners’ awareness regarding prevention and control. A descriptive study with a quantitative approach was conducted, applying surveys to dog owners and collecting fecal samples from 142 dogs across two communities. The Sheather flotation technique was used to identify the parasite, and Pearson’s Chi-square test was applied to assess associations between variables. The results showed that the prevalence of A. caninum was higher in the rural area (51%) compared to the urban area (18%), suggesting that environmental and sanitary conditions influence its transmission. Although most owners (87% in the urban area and 59% in the rural area) implemented deworming measures, no significant association was found between the presence of the parasite and factors such as age, body condition, type of diet, or habitat. The prevalence of A. caninum is not directly related to these variables but is associated with the lack of consistent preventive measures. It is recommended to strengthen deworming strategies, improve hygienic conditions, and promote education on zoonoses to reduce the parasitic burden in the community.